2014
DOI: 10.7314/apjcp.2014.15.11.4583
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Beclin-1 Expression in Colorectal Cancer: a Meta-analysis

Abstract: Objective: Beclin-1 has recently been observed as an essential marker of autophagy in several cancers. However, the prognostic role of Beclin-1 in colorectal neoplasia remains controversial. Our study aimed to evaluate the potential association between Beclin-1 expression and the outcome of colorectal cancer patients. Materials and Methods: All related studies were systematically searched in Pubmed, Embase, Springer and Chinese National Knowledge Infrastructure databases (CNKI), and then a meta-analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 24 publications
2
34
1
Order By: Relevance
“…Multiple previous studies have demonstrated comparable data in line with the present study, in that the loss of BECN1 was reported to be associated with an unfavorable prognosis of several solid cancers, including ovarian carcinoma (15,(25)(26)(27). In contrast, other studies demonstrated that the loss of BECN1 was significantly correlated with improved survival in patients with endometrial cancer, renal cell cancer, and colorectal cancer (28)(29)(30). These differences may be due to a lack of consistency between studies and/or variations in methodologies, or may be disease-specific.…”
Section: Discussionsupporting
confidence: 90%
“…Multiple previous studies have demonstrated comparable data in line with the present study, in that the loss of BECN1 was reported to be associated with an unfavorable prognosis of several solid cancers, including ovarian carcinoma (15,(25)(26)(27). In contrast, other studies demonstrated that the loss of BECN1 was significantly correlated with improved survival in patients with endometrial cancer, renal cell cancer, and colorectal cancer (28)(29)(30). These differences may be due to a lack of consistency between studies and/or variations in methodologies, or may be disease-specific.…”
Section: Discussionsupporting
confidence: 90%
“…Overexpression of BECN1 in patients with resected stage Ⅱ and Ⅲ colon carcinomas who were treated with 5FUbased adjuvant therapy was associated with worse overall survival, supporting a role for autophagy in drug resistance [85] . Moreover, in a metaanalysis, overexpression of BECN1 was associated with a poor prognosis and metastasis in patients with CRC [86] .…”
Section: Becn1 Genementioning
confidence: 98%
“…Nowadays, evidence showed that CRC is a genetic disease and 10-15 % of CRC cases have genetic cause so that one out of 200 individuals has genetic high risk allele for CRC (Fernandez et al, 2002;Turati et al, 2013;Han et al, 2014).…”
mentioning
confidence: 99%